Pengaruh Lama Induksi SILPO Dan Pengaruh Pupuk Gandasil B Terhadap Hasil Dan Kualitas Tanaman Terong (Solanum Melongena L) - Riskika Adikantari; Sugiarto Sugiarto; Abdul Basit (AGRONISMA, 2021)
Eggplant (Solanum melongena L.) is a horticultural plant grown for its fruit. Eggplant production in Indonesia is still low and only contributes 1% of world demand. This study aims to determine the effect of the best duration of SIPLO induction to increase production potential, determine the best dosage of Gandasil B fertilizer to increase production potential, and determine the effect of the interaction between SIPLO induction and double fertilizer B on the growth and yield of eggplant. This study used factorial RAK with two treatment factors. Factor 1 is the duration of the SIPLO induction. Factor 2 is the dose of fertilizer gandasil B. The treatment of factor one, namely S0: SIPLO 0 minutes, S1: SIPLO 60 minutes, S2: SIPLO 90 minutes, S3: SIPLO 120 minutes. The second treatment factors, namely G0 0 grams / liter of Gandasil B, G1 500 grams / liter of Gandasil B, G2 1000 grams / liter of Gandasil B, G3 1500 grams / liter. The treatment combination was 4 x 4 = 16. The total number of samples with 3 replications, namely 16 x 16 x 16 = 48. Each replication was taken 3 plant samples. The results showed that there was a significant interaction effect and separately had a significant effect between the duration of the SIPLO induction and the application of double fertilizer B on the growth and yield of eggplant. The I3G3 treatment (SIPLO 120 minutes and 7g / liter of fertilizer gandasil B) gave the greatest value for plant height with a value of 69.02 cm, number of leaves 25.67, leaf area 398.03 cmÂ², leaf chlorophyll 26.05 mg, fresh weight 1280.27 g Best treatment for the yield parameter of fruit diameter 5.41 cm, 76.52% fruitset, potential production 11.28 tonnes / ha.